SEORANG PENDERITA HEPATITIS KRONIK B DAN C DENGAN MUTASI PADA GEN P53 KODON 249 PADA JARINGAN HATI - Eka Saputra, I Wayan; Gunawan, Stephanus; Muttaqin, Zainul; Soemoharjo, Soewignjo (journal of internal medicine, 2012)
Role of gene P53 as a tumor suppressor gene in generating primary liver cancer is very important primarily in cell growth regulation and apoptosis. By using AS-PCR method, the gene mutation can be recognized. It has been reported a chronic hepatitis B and C case with experiencing mutation of gene P53 Codone 249 in liver tissue of a 33 years old male with anti HCV positive, HBsAg positive, on the liver biopsy indicated of chronic hepatitis without cirrhotic features and malignancy signs. On AS-PCR examination found mutation on gene P53 codone 249. This finding was expected to be an early warning sign for occurrence of primary liver cancer, so that, early intervention could be performed.
Keywords: Gene P53, Chronic Hepatitis